The most effective sexual function and dysfunction interventions in individuals with multiple sclerosis: A systematic review and meta-analysis - Bahare Afshar; Leila Amini; Maryam Hasani; Shayesteh Jahanfar; Seyed Massood Nabavi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Sexual dysfunction has many factors in multiple sclerosis, but there is no reliable treatment for this challenge. Objective: Determining effective sexual function or dysfunction interventions in individuals with multiple sclerosis. Materials and Methods: To find the relevant published interventional studies that at least had an English abstract or in Persian, we searched International Statistical Institute, PubMed, Scopus, Cochrane, Medline, PsycINFO, EMBASE, CINAHL, and Google Scholar from January 1990 to June 2021. The results were analyzed using RevMan 5.3 software. The p < 0.05 was considered significant. Results: Out of 568 articles, 41 were included after deleting the duplicate and irrelevant articles. Studies were divided into 2 groups of sexual function (n = 27) and dysfunction (n = 14). Interventions in each category have 4 subgroups: psychoeducational, exercise and rehabilitation, and medical and multi-type interventions. For improving sexual function, more than half of psychoeducational interventions showed a significant improvement after interventions (p = 0.0003). In sexual dysfunction studies, most of the interventions (n = 13/14) had improved at least one subscale of sexual dysfunction. Medical interventions were effective on men's sexual dysfunction, and psychoeducational interventions had been more effective in women's sexual dysfunction. Conclusion: Psychoeducational and medical interventions are the commonest effective interventions. The psychoeducational studies conducted specifically on women had a positive impact, and only 4 articles with medical interventions were specifically targeted at men, which had a positive effect.